2006
DOI: 10.1111/j.1600-0765.2006.00925.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lN6‐(1‐iminoethyl)‐lysine, an inducible nitric oxide synthase inhibitor, on murine immune response induced by Actinobacillus actinomycetemcomitans lipopolysaccharide

Abstract: It is suggested that treatment with L-NIL in mice immunized with A. actinomycetemcomitans lipopolysaccharide may shift the immune response towards a protective T helper 1-like immunity against A. actinomycetemcomitans-induced infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…The results of the present study further showed that reduced iNOS activity may up‐regulate the production of specific IgG2a by A. actinomycetemcomitans LPS‐activated spleen cells. Increased levels of serum IgG2a in rats with autoimmune interstitial nephritis and in A. actinomycetemcomitans LPS‐immunized mice pretreated with l ‐NIL have also been reported (17, 23). However, the exact mechanism by which the level of splenic A. actinomycetemcomitans LPS‐specific IgG2a was increased by l ‐NIL, as seen in this study, is not well understood.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The results of the present study further showed that reduced iNOS activity may up‐regulate the production of specific IgG2a by A. actinomycetemcomitans LPS‐activated spleen cells. Increased levels of serum IgG2a in rats with autoimmune interstitial nephritis and in A. actinomycetemcomitans LPS‐immunized mice pretreated with l ‐NIL have also been reported (17, 23). However, the exact mechanism by which the level of splenic A. actinomycetemcomitans LPS‐specific IgG2a was increased by l ‐NIL, as seen in this study, is not well understood.…”
Section: Discussionmentioning
confidence: 94%
“…Previously, we and others have shown that Aggregatibacter (formerly Actinobacillus ) actinomycetemcomitans LPS stimulated murine macrophage cell lines and spleen cells to produce NO (14–16). Indeed, treatment with l ‐NIL in mice immunized with A. actinomycetemcomitans LPS resulted in the rapid healing of A. actinomycetemcomitans‐ induced abscess formation, increased levels of serum IFN‐ γ , and specific IgG2a (17). l‐ N 6 ‐(1‐Iminoethyl)‐lysine enhanced the production of IFN‐ γ by LPS‐stimulated rat splenocytes (5), as well as serum IFN‐ γ and IgG2a levels in A. actinomycetemcomitans LPS‐challenged mice (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The protein concentration of the cell lysates was measured using the Bradford protein assay (Bio‐Rad, Hercules, CA). The iNOS activity was assessed as previously described (42). Briefly, 50 μg cell lysate was incubated for 120 min at 37°C in 100 μl 20 m m Tris–HCl (pH 7.9) containing 4 μ m cofactor tetrahydobiopterin (BH 4 ), 4 μ m flavin adenine dinucleotide (FAD), 3 m m dithiothreitol, 2 m m NADPH and 2 m m l ‐arginine.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, we and others have demonstrated that lipopolysaccharide from A. actinomycetemcomitans induces the production of NO by murine macrophages and splenocytes (3, 39, 40). The induction of the immune response to A. actinomycetemcomitans lipopolysaccharide in mice, both in vivo and in vitro , appears to be regulated by NO (42, 43).…”
mentioning
confidence: 99%